The Role Of Organizational Support On The Mental Health Of Lecturers And Education Staff At Mohammad Husni Thamrin University - Atikah Pustikasari; Mahyar Suara (Jurnal Ners, 2026)
Background: Organizational support, also known as Perceived Organizational Support (POS), plays a crucial role in maintaining the mental health of lecturers. When lecturers feel valued and receive attention from the institution, it enhances work engagement, satisfaction, and mental health. Perceptions of organizational support have a significant impact on increasing emotional commitment and work engagement, helping them maintain psychological balance, reduce work stress, and minimize the risk of burnout. Objective: This study aims to analyze the relationship between organizational support and the mental health of lecturers and academic staff at Universitas Mohammad Husni Thamrin. Organizational support was measured using the Perceived Organizational Support (POS) model developed by Eisenberger et al. (1986), while mental health was measured using the Mental Health Continuum-Short Form (MHC-SF), which assesses psychological, emotional, and social well-being. The research method employed a quantitative approach with a cross-sectional design, involving 101 respondents selected using simple random sampling. Results: The results showed that the majority of respondents (62.4%) perceived organizational support as high, and most respondents (52.5%) were categorized as flourishing in terms of mental health, while only 5.9% were categorized as languishing. Bivariate analysis using the chi-square test revealed a significant relationship between organizational support and mental health among lecturers and academic staff, with a p-value of 0.034. These results indicate that the higher the perception of organizational support, the greater the likelihood that lecturers and academic staff experience better mental well-being. Conclusion: The study concludes that organizational support has a significant influence on the mental health of lecturers and academic staff in higher education. Therefore, it is recommended that universities strengthen organizational support policies by enhancing welfare programs for lecturers and academic staff, such as stress management training, psychological counseling services, and work-life balance policies.